Exploring built environment impacts on transit use – an updated meta-analysis. Issue 1 (2nd January 2021) - Aston, Laura; Currie, Graham; Delbosc, Alexa; Kamruzzaman, Md.; Teller, David
ABSTRACT: The built environment (BE) is widely accepted to influence transit use (TU). Evidence to date suggests the relationship is dependent on many factors which can be difficult to account for in quantitative studies. This creates barriers to transferring research into practice. Considering many studies together can be useful for accounting for more of the factors impacting transit use. Yet, meta-analysis of research measuring these influences was last undertaken in 2010 based on 18 studies. Since then 90 new quantitative studies have been published. These recent studies use improved methodologies and are conducted in more diverse geographies. This paper reports an improved and updated meta-analysis of built environment impacts on transit use. It compares elasticity estimates from research published pre-and post-2010 and explores the impact of new methods and a more diverse geographical representation on findings. Updated meta-elasticities range from <0.01 to 0.26; a similar range to the 2010 study. However, at the individual indicator levels, more recent results are different. Elasticities for urban density, including population, employment and commercial density, have increased significantly in studies published since 2010, as did that of land use mix. However, measures of local access, design and jobs-housing balance decreased in post-2010 studies. These results confirm the small but imprecise relationship between the BE and TU. Results also suggest that while the range of elasticity impacts is relatively consistent, new study methodologies, notably those that control for regional accessibility and self-selection, and the increasing geographical diversity in study applications, is acting to change BE-TU findings at the indicator level. Research setting and context are important to consider when using empirical results to design BE strategies to promote transit use.